ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA POP-UP BOOK BERBASIS BUDAYA LOKAL PADA PEMBELAJARAN IPS MATERI KEBERAGAMAN BUDAYA KELAS IV SEKOLAH DASAR - Indri Kurniawati; Pidi Mohamad Setiadi; Anggit Merliana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Social Studies (IPS) instruction in elementary school plays a crucial role in shaping students’ understanding of the nation’s cultural diversity. However, in practice, the effectiveness of such instruction is still hindered by a lack of concrete and contextual learning materials, causing students to struggle with visualizing abstract cultural concepts. This study aims to identify the needs and potential for developing pop-up book learning materials based on local culture for the cultural diversity curriculum in fourth-grade elementary school. This study employs a Research and Development (R&D) approach using the 4D model; this article focuses on the definition (define) stage. Data collection was conducted through observations and interviews with teachers, followed by qualitative descriptive analysis to describe the learning conditions and user needs. The results of the analysis in the define stage indicate that social studies learning is still dominated by the lecture method with limited use of media and does not yet optimally represent local culture. This results in learning that is less interactive and fails to help students understand cultural concepts concretely. Meanwhile, fourth-grade students in the concrete operational stage require visual, tangible, and interactive learning materials. These findings indicate a gap between current learning conditions and students’ needs, highlighting the need for practical, engaging, and contextually relevant materials. Therefore, pop-up books based on local culture are considered a promising solution for enhancing students’ engagement, understanding, and appreciation of cultural diversity.